Salomon Alberti (1540-1600) - S. A. Kutya (Морфологія, 2015)
The University of the German city of Wittenberg is known in Europe largely due to the fact that Martin Luther (1459-1530) and his associate Philip Melanchthon (1497-1560) were taught here, making him the spiritual center of the Reformation. The University is also famous for its medical faculty, which was opened in 1508.